Studi Komparasi Kebertahanan Kota Pasca Bencana Alam - June Ekawati; Gagoek Hardiman; Edward Endrianto Pandelaki (ARSITEKTURA, 2020)
Many cities in the world are geographically located in areas prone to natural disasters. This research is a comparative study that aims to compare the strengths, weaknesses, opportunities and challenges of these cities in the process towards a resilient city despite having a high level of vulnerability to natural disasters. Some cities which are taken as case studies here show a good level of resilience to the disasters experienced. Case studies from this study are three cities namely Kobe, in Hyogo (Japan), Padang (Indonesia) and Camalig (Philippines) which use qualitative descriptive methods with SWOT analysis techniques. From the three cases studied, it was concluded that all three have the same vulnerability due to geographical location, but these three cities also have the capacity as cities that are resilient to disasters with different strengths of capital, which are able to be counterbalanced from vulnerability to resilience.